Li7La3Zr2O12/Polymethacrylate-Based Composite Electrolyte with Hybrid Solid Electrolyte Interphase for Ultra-stable Solid-State Lithium Batteries - Li, Tao; Zhao, Guohao; Zhao, Zhiyi; Xu, Yaqi; Wu, Tianli; Peng, Dong‑Liang; Xie, Qingshui; Xu, Ying (Nano-Micro Letters, 2026)
Li7La3Zr2O12-based electrolytes have got great promise for solid-state lithium (Li) metal batteries because of their high elastic modulus and wide electrochemical stability window. However, the insufficient contact and heterogeneous Li deposition severely hinder their practical applications. Here, a flexible ternary polymethacrylate (PMA) matrix is designed to incorporate with Ta-doped Li7La3Zr2O12 (LLZTO-PMA). The PMA matrix ensures excellent interfacial contact, while the synergistic effects of its polar carbonyl groups and its interaction with LLZTO creating fast interfacial Li+ pathways yield a high ionic conductivity of 0.266 mS cm − 1 at 20 °C. Moreover, the interaction between LLZTO and PMA matrix further guides the formation of a hybrid LiF/Li3N-rich solid electrolyte interphase, which allows a fast Li+ interfacial kinetic due to its lowered Li+ diffusion barrier. Consequently, the LLZTO-PMA electrolyte contributes an ultra-stable Li anode interphase, attaining a lifespan exceeding 10,000 h in symmetric cells and retaining over 96% capacity after 600 cycles in full battery, demonstrating a breakthrough for high-performance solid-state batteries. Highlights: 1 A molecular engineering of Ta-doped Li7La3Zr2O12 (LLZTO) incorporated with polymethacrylate-based (PMA) copolymer moves beyond simple blending to combine the polar carbonyl groups and interfacial Li⁺ transport pathways, yielding high ionic conductivity (0.266 mS cm − 1) and high Li+ transference number (0.621) at 20 °C. 2 The integration of LLZTO triggers the in situ formation of a hybrid LiF-Li3N-rich solid electrolyte interphase with a low Li+ diffusion barrier for uniform Li deposition and exceptional interfacial stability. 3 The LLZTO-PMA contributes an ultra-stable anode interphase, thus delivering symmetric cell over 10,000 h.